When art meets tech: The role of augmented reality in enhancing museum experiences and purchase intentions - He, Zeya; Wu, Laurie; Li, Xiang (Robert) (Tourism management (1982), 2018)
As augmented reality (AR) has been increasingly adopted by various industries as a marketing tool, tourism practitioners have come to recognize its promising potential in staging experiences. Despite the extensive discussions around AR's managerial implications, academic inquiry into how to adopt AR technology in museum tourism contexts remains rare. Building on this emerging stream of scholarly literature, the current study attempts to examine the impact of information type (dynamic verbal vs. dynamic visual cues) and augmenting immersive scenes (high vs. low virtual presence) on visitors' evaluation of the AR-facilitated museum experience and their subsequent purchase intentions. Using an experimental approach, the results demonstrate that compared with dynamic visual cues, dynamic verbal cues lead to visitors' higher levels of willingness to pay more and such effect is more salient when environmental augmentation provides a high level of virtual presence. Such effects can be explained by the psychological mechanism of mental imagery. •This study examines the effects of AR technology's design elements on visitors’ museum experiences and purchasing intentions.•Information type and environmental augmentation were found to jointly influence visitors' willingness to pay a higher price.•Imagery vividness and experiential value were verified astheoretical processes that explain the effects.